Application of Direct Marketing in Function of Improving the Level of Consumer Awareness in the Republic of Serbia - Stanković, Jelena; Đukić, Suzana (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Modern business conditions, the application of information technology and the Internet require the application of a new approach in the process of interactive communication with consumers. Direct marketing, as one of the forms of direct marketing communication, is gaining more and more importance considering that today the business environment is dynamic, competition is more pronounced and there is a growing need to change the way of communicating with consumers. Forms of direct marketing are based on the use of various media, such as: direct mail, telephone, internet, mobile phone, newspapers, magazines, television with direct response. Each media has its advantages and disadvantages in terms of expressive possibilities, costs, scope of information, selectivity of the audience, threshold of visibility and the possibility of renewing messages at certain intervals. Research on direct marketing brings with it numerous challenges, because it requires analysis of the specifics of each technique used and their cross-acting in order to ensure the positive impact of direct marketing on the level of consumer information, which results in satisfied, loyal consumers and creating long-term relationships with them. The aim of this paper is to point out the necessity and importance of direct marketing in the level of consumer information and the creation of a competitive advantage of companies in the Republic of Serbia. Based on the results of empirical research, the importance of certain direct marketing media on informing consumers and making a purchase decision will be analyzed. In this sense, the intention is to identify key consumer habits in terms of the relevance of information obtained through individual direct marketing media based on the age of the respondents, the level of education and monthly income. Such information is crucial in formulating an effective marketing communication strategy. In addition to the importance for business practice, the results of the realized empirical research represent a contribution to the literature and enrichment of existing theoretical views.